Os embates entre ciência e política na experiência parlamentar de Josué de Castro - Menezes, Anna Waleska Nobre Cunha de (2012)
This study want to know how Josué de Castro, the two terms of a congressman, participated in the Brazilian political-ideological debate of the 1950s. For this, search the 61 speeches in the plenary of the House of Representatives and its 14 projects, analyzing them as historical documents that describe an experience, which enables the central category amalgamated the subject and his time, which breaks up the possibilities of new social practices. Unity of action and reflection, the experience of Castro in the Brazilian parliament has got on the basis of a previous flow experiences in the political-institutional and scientific. Together with the personal history, the political intellectual scenario of his time was another variable considered in the first chapter of this work. In the second chapter did an analysis of 32 speeches and projects of the first term of Josué de Castro, grouping them by thematic affinities. The 43 for the second term were discussed in the third chapter, leaving the final considerations answer the research objectives: What are the main interlocutors? What are your political positions? What are the points of rupture and continuity in his political career? Josué de Castro spoke to the Brazilian state directly to the president, some ministers and to the SUDENE, the ONU appears indirectly through the reports of his participations. His political position was a national-developmentalist who embraced the cause of self-determination of the countries, anti-imperialism, agrarian reform and regional planning, strongly inspired by Celso Furtado and San Tiago Dantas. Castro often has blended a liberal and Marxist terminology, relying on different ideologies to do support his fight against hunger